An Analysis of Taboo Words in Megan Thee Stallion Songs - Hanisah Hanafi; Usman Pakaya; Intan Juwita Ahmad (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
Taboo words is forbidden to talk about is connected or dealing of something that must be avoided. Taboo words are also used in the media especially a song. Some songs contain taboo words in their lyrics. Studying taboo words in song lyrics is crucial because it prevents misuse and misinterpretation, ensuring a more accurate understanding of the intended message and artistic expression. It also reveals the moral and cultural values reflected in the lyrics, exposing the societal norms and boundaries that may be challenged or reinforced. This qualitative research addressed the types of taboo words in Megan Thee Stallion songs. The data was analyzed based on Battistella (2005) about the types of taboo words. The researcher uses songs in “Fever” album as the object of the research. The researcher discovered about 21 taboo words in the eight songs on the fever album. The first type is characterized by epithets (6), profanity (2), vulgarity (6), and obscenity (7). According the data, obscenity was the most commonly used type of taboo words in song lyrics. It because there are many expressions involving sex-distinguish anatomy or sexual and excretory functions that is usually spoken harshly. While the research specifically examines Megan Thee Stallion's work, the findings may have broader implications for understanding taboo word usage in songs within the genre. By being aware of and responsibly engaging with taboo words in daily conversations and song lyrics, readers and song lovers can foster a respectful and considerate communication environment. This researcher hoped that readers and song lovers would avoid misusing taboo words that may appear in daily conversations and song lyrics.